Classification of the materials, forming part of the unified agglutinant sands - D. M. Kukuj; I. B. Odarchenco; Ju. I. Lednev (Литьë и металлургия)
There is shown that using of the compound connecting system allows to carry out not only receiving of the stable material but to provide equal distribution along the whole mixture volume of all components, forming part of a compound, as well.